A different viewpoint on mechanism of fracture to shear-banding failure mode transition. (December 2020) - Xu, Zejian; He, Xiaodong; Han, Yang; Huang, Fenglei
Abstract: Fracture to shear-banding failure mode transition (FMT) is an important physical phenomenon in solid materials when a fracture is subjected to dynamic loads. Since its observation, FMT has long been considered as an abrupt change, which is triggered by a critical impact velocity. However, with a novel experimental scheme and a newly-designed dynamic shear fracture specimen, we present a different viewpoint based on experimental observations that FMT is actually not an abrupt change, but a continuous evolving process of distinct microstructures dominated by a thermo-plastic mechanism. The mode II dynamic fracture toughness K IId was determined over a large range of loading rates. It's observed that with the increase of loading rates, K IId rose continuously while the failure modes changed gradually from coalescence of stretched dimples to a combination of dimples and ASBs, and then to extensive ASBs. The initiation and propagation of the fracture was also observed by a high-speed camera, and it has a good consistence with the development of the microstructures in the FMT. This discovery will provide a brand-new understanding to FMT, and lay the foundation for developing of new criteria and theories for selection of failure modes in solid materials. Graphical abstract: Image, graphical abstract